Visualising the voices of nursing: a co-designed video capturing the lived experiences of nurses in Northern Ireland during the COVID-19 pandemic - Carolyn Blair; Dame Anne Marie Rafferty; Paul Murphy; Michael Brown; Karen Bowes; Ruth Thompson; Joanne Reid (BMC Nursing)
Abstract Background Nurses were at the forefront of managing the COVID-19 pandemic. In response, the Royal College of Nursing in Northern Ireland commissioned a longitudinal qualitative survey using the Cognitive Edge SenseMaker® tool to capture nurses’ experiences of delivering care from April 2020 to March 2021. Aim To explore the effect of a co-designed video based on the findings of SenseMaker®, of the lived experience of nurses in Northern Ireland during the 2020/2021 global pandemic. Method Quotes were selected from the SenseMaker® report of nurses’ (n = 676) which conveyed the experiences of nurses during COVID-19. Three co-design workshops were conducted. The first covering the plan for extraction of data from the SenseMaker® report, the second content development and script writing and the third covering feedback and revisions. The video was filmed and edited in the Drama Studies, School of Arts, English and Languages, Queen’s University Belfast. The live launch event took place in the Royal College of Nursing conference venue on 8th February 2024. Data to gauge the effect of the video were gathered via audience participation, MS Teams Version 1.7. chat participation, Mentimeter poll and MS forms survey. The link for the video and survey was accessible via the School of Nursing and Midwifery, Queens University Belfast website after the launch event. The findings were analysed using systematic text condensation using NVivo version 1.6. The study was approved by the Faculty of Medicine, Health and Life Sciences research committee at Queen’s University Belfast following peer review (REC Reference: MHLS 23_100). Results Twenty-eight participants completed the survey; 30 participants attended the live event. Overall, 93% (n = 26) of participants confirmed that the video-based monologues effectively conveyed the emotional perspective and lived experiences of nurses during the COVID-19 pandemic. Four themes emerged - personal reflection and emotional effect, connection and solidarity amidst disappointment, moral injury and resentment, lessons learned and the need for change. Conclusion Wider dissemination of the co-created video-based narratives, with focus on advocacy to policy makers, is needed to prioritise the emotional well-being of nurses and other professionals. There is potential in using video-based monologies to facilitate positive change and better support for professionals, including nursing students in future crises. Further research is needed to assess the broader effect of such healthcare-related research methodologies.